The Influence of Financial Literacy, Income Level and Herding Behavior on Investment Decisions - Nicko Albart (International Journal of Economics Development Research (IJEDR), 2024)
This research aims to determine the influence of Financial Literacy, Income Level, & Herding Behavior on Investment Decisions in PT workers. AA, in Bekasi Regency. The population in this study are workers who work at PT. AA with a sample size of 246 respondents. The sampling technique uses a probability sampling technique with a simple random sampling type. The data in this research was collected using a questionnaire. Data analysis in this test uses multiple linear regression analysis, coefficient of determination test (adjusted R2) and hypothesis testing. The results of this research show that Financial Literacy, Income Level have a significant influence on Investment Decisions. Meanwhile, Herding Behavior does not have a significant influence on Investment Decisions. However, if tested simultaneously, Financial Literacy, Income Level, and Herding Behavior have a significant influence together on Investment Decisions.